2017
DOI: 10.1039/c7gc02211e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient route for the construction of polycyclic systems from bioderived HMF

Abstract: Efficient one-pot synthesis of tricyclic compounds from biobased 5-hydroxymethylfurfural (HMF) is described using a [4 + 2] cycloaddition reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…The diastereomeric configuration was determined by 1 H-NMR and NOE experiments. After considering the NMR data confirmed by the X-ray analysis of HMF-derived norcantharimide analogues obtained in the previous study [ 27 ], the spatial structure of the Diels–Alder adducts was confirmed (see the Supplementary Materials ). Chemical shifts of the diastereomeric protons at the articulated position were characterized by a singlet at ~3.5–3.7 ppm in the 1 H-NMR spectra, while the signals of the appropriate protons in the exo products (compounds norcantharimide [ 28 ] and 10 -exo) were observed in the stronger magnetic fields at ~2.9–3.1 ppm.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The diastereomeric configuration was determined by 1 H-NMR and NOE experiments. After considering the NMR data confirmed by the X-ray analysis of HMF-derived norcantharimide analogues obtained in the previous study [ 27 ], the spatial structure of the Diels–Alder adducts was confirmed (see the Supplementary Materials ). Chemical shifts of the diastereomeric protons at the articulated position were characterized by a singlet at ~3.5–3.7 ppm in the 1 H-NMR spectra, while the signals of the appropriate protons in the exo products (compounds norcantharimide [ 28 ] and 10 -exo) were observed in the stronger magnetic fields at ~2.9–3.1 ppm.…”
Section: Resultsmentioning
confidence: 59%
“…For evaluation of the synthetic potential of the furan ring in the prepared amines, we synthesized norcantharimides 9 – 12 , which were bio-derived analogues of the anticancer drug norcantharidin. We used a modified one-pot protocol based on the Diels–Alder reaction of compounds 6 – 8 with alkenes, followed by hydrogenation of the formed double bond, as reported recently [ 27 ]. The Diels–Alder reactions were performed in THF media at room temperature and monitored by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of two aldehydes groups offers many possibilities for further modification via Wittig reaction, Schiff bases formation, aldol condensation, etc. [24,25] Despite this promise, few reports make use of this compound partly owing to its current high retail price (123 £.g À 1 Sigma Merck accessed 10/3/20) and instability upon prolonged storage. Additionally, the synthesis of DFF from HMF commonly requires molecular oxygen or expensive transition metal (co)-catalyst (e. g. Ru) which further reduces the applicability of DFF-derived reaction at a higher scale.…”
Section: Resultsmentioning
confidence: 99%
“…. 5-HMF is a promising and versatile biomass-based platform molecule from biorefinery carbohydrates, which can be used to produce various chemicals and liquid fuels currently derived from nonrenewable fossil resources [293][294][295][296]. It is worth noting that the production of 5-HMF from renewable cellulose has become an integral part of biorefinery and attracted extensive attention in recent years .…”
Section: -Hydroxymethylfurfural (5-hmf)mentioning
confidence: 99%